Crusade and Mission European Approaches Toward the Muslims. - Kedar, Benjamin Z. (Princeton : Princeton University Press, 2014)
This wide-ranging study of medieval Europe's response to the challenge of Islam examines the relationship between ideas of crusade and mission, between European projects for military conquest and those for the conversion of Muslims to Christianity. Covering the years from the emergence of Islam to the fourteenth century, Benjamin Z. Kedar discusses not only the crusades and the Crusading Kingdom of Jerusalem but also the confrontation of Catholics and Muslims in Sicily and Spain. Originally published in 1988. The Princeton Legacy Library uses the latest print-on-demand te.
Cover; 2. Christian Reconquest and Muslim Conversion ; 4. The Mendicants: Preaching the Gospel to Saracens, Preching the Cross to Christians
Description based upon print version of record.
Keywords: Crusades; Europe -- Relations -- Middle East; Missions to Muslims; Missions, European; Missions to Muslims; Missions, European; Crusades; Europe -- Relations -- Middle East; Middle East -- Relations -- Europe; RELIGION / Christian Ministry / Missions; Electronic books